1996
DOI: 10.1006/viro.1996.0510
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein: Carboxy-Terminal Boundaries of Two Processed Species Suggest Cleavage by a Signal Peptide Peptidase

Abstract: The expression and processing of hepatitis C virus core protein was analyzed. Two protein bands, 21 kDa (P21), corresponding to the full-length core, and 19 kDa (P19), were detected as major products when core protein was expressed in the standard rabbit reticulocyte lysate system or in Sf9 insect cells. Core proteins with amino-terminal hexa-histidine tags were expressed which allowed the purification of the hexa-histidine P19 core with NI(2+)-NTA columns. With the help of mass spectrometry, the molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
138
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 0 publications
8
138
0
1
Order By: Relevance
“…The SPP cleavage site has been proposed to lie between amino-acids 173 and 182 (Fig. 1); when expressed as a single protein in non hepatic cells, HCV core protein was recently shown to end with Phe 177 , but definitive determination of the C-terminus of mature core protein awaits confirmation in a more relevant context [14][15][16][17][18][19]. Based on their apparent molecular masses (aMMs) in sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), the complete and mature forms of HCV core protein are usually referred to as p23 and p21 respectively [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SPP cleavage site has been proposed to lie between amino-acids 173 and 182 (Fig. 1); when expressed as a single protein in non hepatic cells, HCV core protein was recently shown to end with Phe 177 , but definitive determination of the C-terminus of mature core protein awaits confirmation in a more relevant context [14][15][16][17][18][19]. Based on their apparent molecular masses (aMMs) in sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), the complete and mature forms of HCV core protein are usually referred to as p23 and p21 respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their apparent molecular masses (aMMs) in sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), the complete and mature forms of HCV core protein are usually referred to as p23 and p21 respectively [9]. However, it remains unclear whether SPP-catalysed cleavage to liberate p21 is absolutely dependent on prior cleavage by SP to generate p23 from the polyprotein [15,16,20,21]. Indeed, Lemberg and Martoglio have proposed the general rule that cleavage by SP is a prerequisite for cleavage by SPP [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, transgenic mice expressing HCV core protein developed liver steatosis and thereafter hepatocellular carcinoma (34,36). Thus, it has been suggested that HCV core protein is a multifunctional molecule that acts as a structural protein but is also involved in the pathogenesis of hepatitis C. HCV core protein has two major forms, p23 and p21 (16,25,31,43,53). HCV core protein p23 represents a 191-amino-acid product in which the C-terminal hydrophobic region also acts as a signal sequence for E1.…”
mentioning
confidence: 99%